Effect of water entrainment by pre-soaked biochar particles on strength and permeability of cement mortar - Gupta, Souradeep; Kua, Harn Wei (Construction & building materials, 2018)
•Internal curing in mortar by water entrainment in pores of biochar is proposed.•Moisture retention and hydration degree are increased due to addition of pre-soaked biochar.•Increase in mechanical strength is observed in pre-soaked biochar mortar under wet curing and dry curing conditions.•Improved water tightness is achieved under wet and dry curing due to addition of dry and pre-soaked biochar. Water retention by biochar makes it a potential material for soil enhancement. However, its application as an internal curing agent in cementitous matrix is relatively unexplored. This study explores addition of pre-soaked biochar on strength and permeability of cement mortar, subject to moist curing and air curing respectively. Biochar was prepared from mixed wood saw dust at pyrolysis temperature of 300 °C (BC 300) and 500 °C (BC 500) respectively. Biochar particles were saturated with water prior to addition in mortar mix at 2 wt% of cement. Experimental results show that mortar with pre-soaked BC 300 and BC 500 offer 40–50% higher compressive strength at 28-day compared to plain mortar, especially under air curing condition. Similar trend is observed for flexural and split-tensile strength. It is linked to initially low water-cement ratio of mixes with pre-soaked biochar and internal availability of moisture from pores of biochar under external dry condition. Water accessible porosity was reduced by 18–20% due to addition of pre-soaked biochar, that resulted in reduction of sorptivity and depth of water penetration by 55–60%. Overall, significant improvement in mechanical and permeability properties were observed when pre-soaked biochar is used compared to addition of dry biochar in mortar, especially in absence of external moist curing. The internal curing efficiency of pre-soaked biochar on mortar was found to be higher compared to other mixes, which suggests that it can be a potential curing material for cement mortar. Using biochar as additive in cement mortar also ensures higher waste recycling and carbon sequestration in civil infrastructure while improving strength and durability performance.